BERSUCI DAN BERIBADAH SHALAT BAGI PASIEN LUKA BAKAR - Khair, Fathul; Pratama, Kharisma (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
This study aims to examine procedures for purifying and performing prayers for patients with severe burns, who often have physical limitations so they cannot perform worship using conventional methods. Using a qualitative descriptive approach with content analysis techniques and library research, this research provided a guidance for patients with severe burns in worship. The research results show three main points: first, the condition of patients with severe burns occurs as an emergency or near emergency, where patients are not advised to come into contact with air or make many movements. Second, patients in this condition are allowed to replace ablution with tayammum as a way of purifying themselves. Third, considering their physical limitations, patients are allowed to pray with adapted movements, for example praying in a sitting, lying position, or whatever is possible. This research is important to ensure that patients with severe burns can still carry out their worship according to Islamic regulations, even in limited physical conditions.